ANALISIS PENERAPAN ASESMEN DIAGNOSTIK DALAM PEMBELAJARAN MATEMATIKA DI SMP YP PGRI 4 MAKASSAR - Khaerani Khaerani; Rahmawati Rahmawati; Syamsuriyawati Syamsuriyawati; Rahmat kamaruddin (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
This research is motivated by the independent curriculum which has begun to be implemented in several schools by implementing inclusive learning, where every child gets equal opportunities in education regardless of the child's condition. To support the implementation of inclusive education, the first thing every teacher needs to do before starting the learning process is a diagnostic assessment. The purpose of this study was to analyze and describe the application of diagnostic assessment of algebraic material to class VII students of SMP YP PGRI 4 Makassar. The research subjects were 30 class VII students of SMP YP PGRI 4 Makassar. This type of research is descriptive qualitative. Collecting data using diagnostic assessment and interviews. The research data are combined to determine the classification of students' answers. The results showed that 16.67% of students were in the complete understanding category, 10% were in the misconception category, 3.33% were in the guessing category, 50% were in the lack of understanding category, and 20% were still in the do not understand category.